Complete Mitochondrial Genome of the Fungal Biocontrol Agent Trichoderma atroviride: Genomic Features, Comparative Analysis and Insight Into the Mitochondrial Evolution in Trichoderma - Kwak, Yunyoung (Frontiers in Microbiology, 2020)
The improvement of biopesticides for use in the agriculture industry requires an understanding of the biological- and ecological principles underlying their behavior in natural environments. The nuclear genomes of members of the genus Trichoderma, which are representative fungal biocontrol agents, have been actively studied in relation to the unique characteristics of these species as effective producers of CAZymes/secondary metabolites and biopesticides, but their mitochondrial genomes have received much less attention. In this study, the mitochondrial genome of Trichoderma atroviride (Hypocreales, Sordariomycetes), which targets wood-decaying fungal pathogens and has the ability to degrade chemical fungicides, was assembled de novo. A 32,758 bp circular DNA molecule was revealed with specific features, such as a few more protein CDS and trn genes, two homing endonucleases (LAGLIDADG-/GIY-YIG-type), and even a putative overlapping tRNA gene, on a closer phylogenetic relationship with T. gamsii among hypocrealean fungi. Particularly, introns were observed with several footprints likely to be evolutionarily associated with the intron dynamics of the Trichoderma mitochondrial genomes. This study is the first to report the complete de novo mitochondrial genome of T. atroviride, while comparative analyses of Trichoderma mitochondrial genomes were also conducted from the perspective of mitochondrial evolution for the first time.